Peningkatan Kualitas Desa Menciptakan Lingkungan yang Sehat, Tanggap, Asri, dan Bijak dalam Menjaga Lingkungan di Desa Muara Kumpeh Kabupaten Muaro Jambi - Ahmad Kusuma; I Wayan Karmana; Sandika Ardiansyah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this activity is to create a healthy, responsive, beautiful and wise environment in protecting the environment in Muara Kumpeh Village, Muaro Jambi Regency. The methods used include: 1) making observations; 2) submission of proposals; 3) collection of seeds; 4) distribution of seeds; and 5) planting on village land. The results of the dedication obtained were the handling of excess waste in Muara Kumpeh Village by recycling waste such as used bottles which were used as flower pots and also other waste. Reforestation of Muara Kumpeh Village by planting 1,500 productive and non-productive tree seedlings, namely 300 durian seeds, 300 avocado seeds, 300 sengkol seeds, 300 neem seeds, 150 teak seeds, 150 mahogany seeds. and also distributed it with the farmer groups of Muara Kumpeh Village to the community.